IMPROVEMENT OF CONCEPTUAL APPROACHES TO THE FORMATION OF COMPETITIVE ADVANTAGES OF RETAIL TRADE ENTERPRISES - DRAZHNYTSIA, Sergii; NOVOSAD, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In this article, the authors specify the essence and meaning of competitive advantages, as the main means of successful functioning of retail enterprises in the competitive market, their structure and functions. The article examines the civilizational development of approaches to the formation of competitive advantages of enterprises, as well as, on the basis of generalization, specifies the definition of the concept of formation of competitive advantages of retail trade enterprises. In the article, the authors also analyzed the principles and structure of existing concepts of the formation of competitive advantages of retail enterprises, and identified their common and distinctive features. It was determined that any concept contains theoretical and applied bases, which, in turn, form a set of theoretical and methodological principles and organizational and applied approaches to its implementation. The main idea of the concept of the formation of competitive advantages of retail trade enterprises is to increase the competitiveness of trade enterprises under modern conditions. Based on the analysis, the authors proposed an author’s version of the concept of the formation of competitive advantages of retail enterprises, the basis of which is the life cycle of the competitive advantages themselves.